2018
DOI: 10.1039/c7cp06196j
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring electronic properties of multilayer phosphorene by siliconization

Abstract: Controlling the thickness dependence of electronic properties for two-dimensional (2d) materials is among the primary goals for their large-scale applications. Herein, employing a first-principles computational approach, we predict that Si interaction with multilayer phosphorene (2d-P) can result in the formation of highly stable 2d-SiP and 2d-SiP compounds with a weak interlayer interaction. Our analysis demonstrates that these systems are semiconductors with band gap energies that can be governed by varying … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…Although LDOS in known to provide a good insight into the spatial distribution of electronic properties, 31,35,66,67 the computed quantity can be affected by the limitations of the projection scheme utilizing spherical approximation of the Wigner-Seitz cells. 68 In particular, the surface charge densities estimated from the layer-resolved LDOS (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although LDOS in known to provide a good insight into the spatial distribution of electronic properties, 31,35,66,67 the computed quantity can be affected by the limitations of the projection scheme utilizing spherical approximation of the Wigner-Seitz cells. 68 In particular, the surface charge densities estimated from the layer-resolved LDOS (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, recent studies have shown that the prediction of vdW forces remains the challenge despite new developments in the vdW field. [50][51] Specifically, it has been shown that all common approaches to treat vdW forces overestimate interlayer interaction energy in layered systems when compared to diffusion Monte-Carlo simulations. 50 Moreover, existing XC functional has a limitation to describe chemical potentials of elemental reference states.…”
Section: Role Of the XC Functionalmentioning
confidence: 99%
“…The synthesis of 2D SiP by mechanical exfoliation of the bulk material appears thus to be feasible. By using molecular dynamics calculations, Zhang et al 9 showed that 2D SiP is dynamically and thermodynamically stable even at 900 K. Moreover, it was found that the electronic/optical properties of 2D SixPy alloys 10 can be tuned either by varying the thickness 8,11 , the stacking 11 or by application of an in-plane strain 8,12,13,14 . Interestingly, a transition from an indirect to a direct bandgap has been predicted when SiP is thinned down to a monolayer 8,9 .…”
Section: Introductionmentioning
confidence: 99%